The Mediating Role of Interactive Multimedia on the Relationship Between Perceived Usefulness and Learning Engagement in Mobile Learning Environments: A TAM Perspective - Saputra, Ageng Dian; Firdaus, Rangga (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Mobile-based distance learning has become a dominant paradigm in higher education; however, the sustainability of student participation remains a critical challenge that has not been fully explained by the conventional Technology Acceptance Model (TAM). This study aims to extend TAM by integrating the mediating role of interactive multimedia in the relationship between perceived usefulness and learning engagement, as well as evaluating the influence of multimedia richness on students’ continuance intention in mobile-based distance learning. This study employed a quantitative approach with a cross-sectional survey design involving 387 students enrolled in distance education programs in Indonesia. The research instrument consisted of a structured questionnaire using a 5-point Likert scale, which was validated through convergent and discriminant validity tests. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings revealed that interactive multimedia significantly mediates the relationship between perceived usefulness and learning engagement, while multimedia richness strengthens perceived usefulness, which in turn enhances students’ continuance intention. The main conclusion confirms that the integration of rich interactive multimedia is a key predictor in sustaining students’ continuous participation in mobile learning platforms. This study contributes to the development of a more comprehensive TAM framework and provides practical guidance for e-learning platform developers in designing more engaging and sustainable learning experiences.